PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOPER BRAND LOJEL PADA DEPARTMENT STORE METRO DI MALL GANDARIA CITY JAKARTA - Tambunan, Dewi; Mustakim, Masran (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of product quality and price on purchasing decisions for Lojel brand suitcases at the Metro Department Store at Gandaria City Mall, Jakarta, either partially or simultaneously. The research method used is quantitative. The population in the study was 2,160 respondents. With a sampling technique using random sampling, a sample of 96 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research results show that product quality has a significant effect on purchasing decisions with a simple regression equation Y = 27.334 + 0.396 X1. Hypothesis testing obtained a calculated t value > t table or (6.480 > 1.986). Thus, Ho1 is rejected and Ha1 is accepted, meaning that there is a significant influence of product quality on purchasing decisions. Price has a significant effect on purchasing decisions with the simple regression equation Y = 16.349 + 0.638 X2. Hypothesis testing obtained a calculated t value > t table or (9.318 > 1.986). Thus, Ho2 is rejected and Ha2 is accepted, meaning that there is a significant influence of price on purchasing decisions. Product Quality and Price on Purchasing Decisions with the multiple regression equation, namely Y = 12.087 + 0.226X1 + 0.513X2. Hypothesis testing obtained a calculated F value > F table or (59.708 > 3.094). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous influence of product quality and price on purchasing decisions.